Serological surveillance on potential Plasmodium vivax exposure risk in a post-elimination setting - Huang, Fang; Cui, Yanwen; Huang, Zhuoying; Wang, Siqi; Li, Shigang; Guo, Xiangrui; Guo, Xiang; Xia, Zhi-Gui (Frontiers in Cellular and Infection Microbiology, 2023)
China was declared malaria free in June of 2021. In the post-elimination setting, vigilant surveillance is essential to sustain malaria free status. Serological surveillance has been recognized as an efficient tool for assessing the immunity levels and exposure risk in a population. In this study, a cross-sectional serological survey was conducted in Yingjiang County, China, in August–September, 2021. The study sites were villages along the borders with Myanmar, which have no local transmission since the last indigenous cases registered in 2016. A total of 923 participants from six villages were enrolled. The majority was aged > 36 years (56.12%) and 12.46% (115/923) participants had experienced malaria infection at least once. A magnetic- bead-based assay was used to test antibodies against Plasmodium vivax antigen PvMSP-119 to evaluate the prevalence of antibody positive subjects. A reversible catalytic model was used to assess the risk of exposure. The prevalence of anti-PvMSP-119 IgG was 12.84% [95% confidence interval (CI): 9.22%–16.47%], 13.93% (95% CI: 10.11%–17.74%), and 3.57% (95% CI: 1.40%–5.75%) in three different line-of-defense areas, which differed significantly (P < 0.0001). The prevalence of anti-PvMSP-119 IgG increased with age and no statistically significant difference was detected between the sexes. The reversible catalytic model indicated that the seropositive conversion rate and seronegative reversion rate were 0.0042, 0.0034, 0.0032 and 0.0024, 0.0004, 0.0065 in the first-, second-line-of-defense area and total areas, respectively, and the fitted value did not differ significantly from the observed value (P > 0.1). Although this study found the prevalence of antibody-positive subjects and the seroconversion rate in this post-elimination setting were lower than that in transmission setting, the population still had an exposure risk. Serological surveillance should be considered in post-elimination settings to provide valuable information with which to evaluate the risk of malaria re-establishment.